Production Politics: Gender, Feminism, and Social Media Labor - Pruchniewska, Urszula; Duffy, Brooke Erin (AoIR Selected Papers of Internet Research, 2016)
Amidst radical transformations in the technologies, politics, and markets of cultural labor, critical studies of the so-called digital economy abound. This project brings considerations of gender, femininity, and feminism to the fore of debates about emergent worker subjectivities in an age of social media. Drawing upon in-depth interviews with digital/social media producers across genres and platforms, we explore some of the key tensions and contradictions that structure gendered work in online contexts: feminist politics and post-feminist articulations of selfhood; individualized self-branding and collective mobilization; and empowerment and exploitation.